Effects of Dietary Inclusion of Prebiotic, Probiotic and Synbiotic on the Intestinal Glucose Absorption of Broiler Chickens - Awad, W.A.; Ghareeb, K.; Nitsch, S.; Pasteiner, S.; Abdel-Raheem, S.; Böhm, J. (International Journal of Poultry Science, 2008)
Due to growing concerns about antibiotic resistance and the potential for a ban for antibiotic growth promoters, there is an increasing interest in finding alternatives to antibiotics in poultry production. The effects of prebiotics and probiotics or direct fed microbials (DFM) on gut health and performance in poultry as well as other species are studied. The interactions between intestinal microbiota, the gut epithelium and the immune system are important in the competitive exclusion process. Such feed additives have already been shown to affect relevant functions of the intestinal mucosa such as lowering the secretory response to theophylline or stimulating sodium/glucose cotransport in rat, but knowledge of the plausible interactions between food contaminants and natural components has not yet been studied. In this study we examined the effects of prefeeding of a microbial feed additive (Lactobacillus sp.), prebiotic (chicory rich in inulin) and synbiotic feed additive (combination of probiotic strain Enterococcus faecium, prebiotic chicory rich in inulin and immune stimulating substances derived from sea algae) on glucose transport of isolated jejunal mucosa of broiler chicks in the presence or absence of deoxynivalenol by the Ussing chamber technique. The addition of glucose on the mucosal side in Ussing chamber produced a significant increase in short-circuit current (Isc) (P < 0.001) in all treated groups relative to the basal values. This increase in Isc for prebiotic and probiotic feed additives is equivalent to an increase of about 2 times that for the basal values and 3 times for the synbiotic group, while in the control group is about half fold that for the basal value. Further addition of DON to the mucosal solution decreased the D-glucose-stimulated current and returned to the basal value. In the second experiments, the addition of D-glucose to the mucosal side after preincubation of the control tissues with DON had no effect on the Isc (P > 0.05). While, the glucose addition after preincubation of the tissue with DON produced a higher increase in the Isc from the basal values in the prebiotic group (70%), probiotic group (20%) and the synbiotic group (26%) compared with the control group (13%), suggesting that the dietary prebiotic, probiotic and synbiotic supplementation of the broilers increased the glucose transport in the presence of DON which could be promising to reduce the alterations caused by DON on gut physiology. This may offer the host protection against the negative effects of DON on intestinal glucose absorption. Thus, this study supports the concept that probiotics, prebiotic and synbiotic may exert beneficial effects in the gastrointestinal tract.